Retrograde trans-synaptic degeneration of visual pathway in an adult with head injury - Thomas Arun Varghese; Annamma James; Cigia Paul (Kerala Journal of Ophthalmology, 2016)
A 41-year-old male with a history of head injury 16 years previously but no visual deficit, presented with reading difficulty. Examination showed disc pallor bilaterally, and perimetry showed the left homonymous hemianopsia. Optical coherence tomography showed a reduction of retinal nerve fiber layer temporally in the right eye and nasally in the left eye correlating with the field defect. Magnetic resonance imaging brain showed atrophy of the right half of chiasma and right optic tract, indicating retrograde degeneration of the right visual pathway.